Thyroidectomy with Drain and Without drain; A Clinical Comparative Study - Saleem, Muhammad; Saba, Sarwat; Saqib, Khurram; Alamgir, Ashar; Tabassam, Sumara; Rashid, Zakariya (Journal of Rawalpindi Medical College, 2023)
Background: Thyroidectomy is one of the most difficult surgical procedures. The study aims to compare the thyroidectomy procedure with drain placement and without drain concerning the hospital stay, Postoperative complications, and pain assessment using a visual analog scale. Methods: A prospective comparative study was designed in the Department of otorhinolaryngology & Head Neck Surgery---removed for blind review----. A total of 117 patients were enrolled in the study from which 9 were excluded due to loss of follow-up. The patients were divided into two groups by using computer-generated randomized numbers containing sealed envelopes. Both groups contained 54 patients. Group A patients with a drain placed while group B contained patients without a drain. The patients with drain have a longer hospital stay and reported increased pain as compared to the patients with drainless thyroidectomy. Results: The mean age and standard deviation calculated for the patients enrolled in both groups after randomization was 13.28 42.5 and 12.18 43.9 in groups A and B respectively. The mean ages were statistically insignificant. However, Postoperative variables such as length of hospital stay and post-operative pain by visual analog scale were assessed. The hospital stays of the patients with a drain placed was found statistically significant with a P-value < 0.05 Postoperative pain assessed by visual analog scale was also significant having a P-value <0.05 for patients having stayed for 2 to 4 days. Conclusion: Placement of drain after thyroidectomy saves the patient from life-threatening complications but at the same time increases the post-operative pain on day one and increases the length of hospital stay of the patient. The routine practice of drain placement should be avoided unless there must be a risk of the development of hematoma or seroma.